Evaluation of Wild Flora Surrounding Blueberry Fields as Viable Hosts of Drosophila suzukii (Matsumura, 1931) (Diptera: Drosophilidae) in Georgia - Joshua A. Grant (Insects, 2021)
Drosophila suzukii, an economically important pest of small and thin-skinned fruits, has caused annual crop losses up to 20% in the state of Georgia’s multimillion-dollar blueberry industry. The known host range of D. suzukii is large, yet the breadth of uncultivated and wild plants that can serve as alternative hosts in the southeastern United States is still not fully understood. Establishing comprehensive lists of non-crop D. suzukii hosts in woodlands near blueberry production will assist in the creation of more sustainable integrated pest management (IPM) strategies. Objectives of this study were to determine viability of wild fruiting plant species to this pest based on survivorship to adulthood and assess D. suzukii short-range preference between cultivated blueberries and wild fruit. Laboratory choice and no-choice assays were performed to determine if D. suzukii could complete its development on wild fruits sampled from the field. Results from our no-choice assays indicated that multiple species of wild fruits surveyed in Georgia were viable D. suzukii hosts including blackberry species, deerberry, hillside blueberry, common pokeweed, beautyberry, elderberry, evergreen blueberry, and large gallberry. Yet, none of these hosts were preferred by adult female D. suzukii as ovipositional substrates when compared to cultivated blueberries. However, these uncultivated species have the potential to sustain D. suzukii populations pre- and post-harvest season. This information can help farmers do more targeted management of these viable alternative hosts from wooded areas surrounding blueberry fields in order to minimize D. suzukii populations.